2017
DOI: 10.1136/bmjsrh-2017-101825
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with condom use among men and women living with HIV in Lilongwe, Malawi: a cross-sectional study

Abstract: Background Understanding the influences on condom use among men and women living with HIV is critical to tailoring sexually transmitted infection/HIV prevention efforts. Methods This is a sub-analysis of a cross-sectional survey including 255 women and 220 men who were sexually active, HIV-positive, and attending HIV care visits in Lilongwe, Malawi. We estimated adjusted prevalence ratios (aPRs) to evaluate for factors associated with consistent condom use (always using condoms in the past month) and use at la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
7
13
4
Order By: Relevance
“…Although women who used condoms during last vaginal intercourse cited HIV prevention as their main reason for condom use, the decreased rate of consistent condom use during the previous six-month period demonstrates that other factors influenced their actual practices over multiple sexual episodes. This is also supported by the trend toward reduced condom use in women who reported greater sexual frequency, which has been seen in other studies [10, 23].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although women who used condoms during last vaginal intercourse cited HIV prevention as their main reason for condom use, the decreased rate of consistent condom use during the previous six-month period demonstrates that other factors influenced their actual practices over multiple sexual episodes. This is also supported by the trend toward reduced condom use in women who reported greater sexual frequency, which has been seen in other studies [10, 23].…”
Section: Discussionsupporting
confidence: 83%
“…Many of the previous studies that have examined condom use practices in HIV-positive adult women were done in sub-Saharan Africa where HIV rates are much higher compared to the U.S. [810]. However, these populations may not be generalizable due to socio-economic, cultural, and religious differences.…”
Section: Introductionmentioning
confidence: 99%
“…This is crucial, noting that, as the war against the HIV epidemic advances globally, massive gain will largely depend on everyone taking responsibility being accountable to their sexual behaviors. This finding is consistent with a recent study in Mozambique which found that knowledge of HIV–positive status (a proxy for testing) is associated with more frequent condom use,30 and several others,31,32 thus corroborating the known positive correlation between health knowledge and health practice 33. It is also argued that knowledge is imperative for social transformation and has been considered as a key factor in enhancing decision-making among individuals 34…”
Section: Discussionsupporting
confidence: 91%
“…However, unlike condoms, these methods are unable to prevent sexually-transmitted infections [28]. Even when women desire consistent condom use, gender power imbalances may affect their ability to negotiate with their partners [3133]. The practical and socio-cultural challenges of condom use (whether alone or as dual protection) among HIV-affected couples need to be further explored, with the development of counter-strategies in mind.…”
Section: Discussionmentioning
confidence: 99%